CHALLENGES AND RESPONSIBILITIES OF MEDAN SOCIAL SERVICES: A CASE STUDY OF ARTICLE 105 KHI AND THE WELFARE OF ABANDONED CHILDREN - Siagian, Muhammad Fahmi; Ja’far, Hasbullah (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
The purpose of this research is to examine the implementation of Article 105 of the Compilation of Islamic Law (KHI), focusing on the protection and support for abandoned underage children in Medan. Although Article 105 of KHI designates the mother as the primary guardian for minors, a significant number of children are still abandoned by their mothers, often left to live on the streets. The Medan Social Services Department, as a government agency, plays a critical role in addressing and reducing the prevalence of abandoned minors by providing essential support and care. A qualitative case study methodology was employed, with data collected through document analysis and interviews with officials at the Social Services Department of Medan. This approach allowed for an in-depth examination of the department’s responsibilities, the specific measures implemented to safeguard underage children, and the challenges encountered in fulfilling these duties. The findings reveal that while the Social Services Department in Medan works to implement Article 105 KHI by facilitating support services for neglected children, it faces substantial challenges, including limited resources, inadequate funding, and staffing shortages, which impact the effectiveness of care provided. These limitations highlight the need for ongoing development in both policy and practical support. This study contributes original insights into the operationalization of KHI regulations concerning child welfare in a municipal context, emphasizing the role of government intervention where parental responsibility is lacking. The implications suggest that increased resource allocation and inter-agency collaboration are necessary to enhance the protection of vulnerable minors, contributing valuable perspectives to both child welfare policy and Islamic legal studies on child guardianship.